2020
DOI: 10.1177/2055217320912789
|View full text |Cite
|
Sign up to set email alerts
|

Cost-efficiency of specialist inpatient rehabilitation for adults with multiple sclerosis: A multicentre prospective cohort analysis of the UK Rehabilitation Outcomes Collaborative national clinical dataset for rehabilitation centres in England

Abstract: Background: Rehabilitation is effective for multiple sclerosis, but is it value for money? Objectives: To evaluate functional outcomes, care needs and cost-efficiency of specialist inpatient rehabilitation for adults with multiple sclerosis (MS). Methods: A multicentre cohort study of prospectively collected clinical data from the UK Rehabilitation Outcomes Collaborative national clinical database. Data included all adults with MS (n ¼ 1007) admitted for specialist inpatient (Level 1 or 2) rehabilitation in En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Other FIM efficiency values from large population-based samples of people with stroke have ranged from 0.48 (95% CI: 0.15, 0.89; n =1995) [27] to 1.59 [19]. The only large sample study of FIM efficiency in people with MS reported a value of 0.23 (95% CI: 0.22, 0.23) over the period 2010 to 2018 [28] considerably lower than ours, although for the same time period. One of the differences between our study and one from UK was the average length of stay was 39 days in Canada and 59 days in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…Other FIM efficiency values from large population-based samples of people with stroke have ranged from 0.48 (95% CI: 0.15, 0.89; n =1995) [27] to 1.59 [19]. The only large sample study of FIM efficiency in people with MS reported a value of 0.23 (95% CI: 0.22, 0.23) over the period 2010 to 2018 [28] considerably lower than ours, although for the same time period. One of the differences between our study and one from UK was the average length of stay was 39 days in Canada and 59 days in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary rehabilitation in MS is also good value for money in terms of its cost-effectiveness. 33 Unfortunately, unlike in many northern hemisphere countries, MS-specific multidisciplinary rehabilitation services (ie teams including cognitive rehabilitation specialists as well as other rehabilitation specialists) are not readily available in Australia; they are not available in most states and territories, and certainly not in rural or remote settings. Fortunately, cognitive rehabilitation as a stand-alone intervention is nevertheless a viable option.…”
Section: Next Steps: Choosing Between the Effective Cognitive Rehabil...mentioning
confidence: 99%